2022
DOI: 10.1073/pnas.2116007119
|View full text |Cite
|
Sign up to set email alerts
|

Yeast cells actively tune their membranes to phase separate at temperatures that scale with growth temperatures

Abstract: Membranes of vacuoles, the lysosomal organelles of Saccharomyces cerevisiae (budding yeast), undergo extraordinary changes during the cell’s normal growth cycle. The cycle begins with a stage of rapid cell growth. Then, as glucose becomes scarce, growth slows, and vacuole membranes phase separate into micrometer-scale domains of two liquid phases. Recent studies suggest that these domains promote yeast survival by organizing membrane proteins that play key roles in a central signaling pathway conserved among e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 73 publications
(141 reference statements)
3
19
0
Order By: Relevance
“…Ergosterol is the major sterol in yeast, and it has been suggested that phase separation of vacuole membranes could be due to an increase in ergosterol (8). An increase in ergosterol would be consistent with a report that the ratio of filipin staining of sterols in vacuole versus plasma membranes is higher in the stationary stage than the log stage, although vacuole and plasma membrane levels were not measured independently (10, 15). It would also be consistent with the expectation that esterified sterols in lipid droplets are mobilized in the stationary stage by lipophagy, which is required for the maintenance of phase separation in the vacuole membrane (17, 21, 33, 37).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Ergosterol is the major sterol in yeast, and it has been suggested that phase separation of vacuole membranes could be due to an increase in ergosterol (8). An increase in ergosterol would be consistent with a report that the ratio of filipin staining of sterols in vacuole versus plasma membranes is higher in the stationary stage than the log stage, although vacuole and plasma membrane levels were not measured independently (10, 15). It would also be consistent with the expectation that esterified sterols in lipid droplets are mobilized in the stationary stage by lipophagy, which is required for the maintenance of phase separation in the vacuole membrane (17, 21, 33, 37).…”
Section: Resultssupporting
confidence: 91%
“…An obvious candidate for a bait protein was Vph1, which has high expression levels in the log stage (8, 31). Vph1 has been extensively used for visualizing vacuole domains (5, 7–10, 15), and was previously used by us to demonstrate the utility of MemPrep for isolating vacuole membranes in the log stage (25). However, in the stationary stage, expression levels of Vph1 are lower (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations